(untitled) (PERcursos Linguísticos, 2020)
ABSTRACT: The present paper aimed to reflect about the main theoretical notes around gesture developed by Volóchinov in two of his texts of the first half of the twentieth century: Discourse in Life and Discourse in Art (1926) and the Construction of the Utterance (1930). As theoretical contribution, we used the theoretical and methodology assumptions of Bakhtin Circle, specially the considerations of Valentin Volóchinov. We highlighted that the investigation of our research was bibliography, once we support each other in essays already published to summarize the ideas and to develop reflections concerning of them. We emphasize that, in the course of our reflections, we were used some cartoons that help us in the process of the construction of our argument. The results revealed that, in constructing the essays, Volóchinov points out, even though briefly, the questions about gesture. In Discourse in Life and Discourse in Art: To the sociological poetic, we verify that the gesture is linked to the notion of extraverbal, as well as in the shared and implied character of the evaluations of a specific social group, and the personification of the third participant. While, In the Construction of the Utterance, we observed that the gesture is relate to the notion of reply (response) and the idea of social orientation of utterance. KEY WORDS: Gesture. Volóchinov. Essays of 1926 e 1930. Utterance.